Intracellular Adhesion Molecule-1 (ICAM-1) Levels in Convalescent COVID-19 Serum: A Case Report - Smith-Norowitz, Tamar A; Loeffler, Jeffrey; Norowitz, Yitzchok M; Kohlhoff, Stephan (Annals of clinical and laboratory science, 2021)
Intercellular adhesion molecule-1 (ICAM-1), an endothelial cell adhesion molecule, contributes to inflammation and immune-mediated responses. Viral infection of endothelial cells caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause vascular changes and elevate the expression of ICAM-1 in coronavirus disease 2019 (COVID-19) patients and may be used as a biomarker to measure disease severity or recovery. This study sought to identify the ICAM-1 levels in convalescent COVID-19 serum 2 to 33 weeks after the initial diagnosis.OBJECTIVEIntercellular adhesion molecule-1 (ICAM-1), an endothelial cell adhesion molecule, contributes to inflammation and immune-mediated responses. Viral infection of endothelial cells caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause vascular changes and elevate the expression of ICAM-1 in coronavirus disease 2019 (COVID-19) patients and may be used as a biomarker to measure disease severity or recovery. This study sought to identify the ICAM-1 levels in convalescent COVID-19 serum 2 to 33 weeks after the initial diagnosis.ICAM-1 levels were measured 2-33 weeks after COVID-19 diagnosis (April 2020) in the serum from a subject in Brooklyn, New York who recovered from COVID-19 (ELISA). SARS-CoV-2 IgG antibody levels were also measured (ELISA).METHODSICAM-1 levels were measured 2-33 weeks after COVID-19 diagnosis (April 2020) in the serum from a subject in Brooklyn, New York who recovered from COVID-19 (ELISA). SARS-CoV-2 IgG antibody levels were also measured (ELISA).ICAM-1 levels were low 2 weeks after the initial COVID-19 diagnosis and increased 6-fold at 5 weeks. ICAM-1 levels decreased at 12 weeks (50%) and at 33 weeks (50%) after the initial COVID-19 diagnosis. SARS-CoV-2 IgG antibody levels were detected 4-5 weeks after the initial COVID-19 diagnosis.RESULTSICAM-1 levels were low 2 weeks after the initial COVID-19 diagnosis and increased 6-fold at 5 weeks. ICAM-1 levels decreased at 12 weeks (50%) and at 33 weeks (50%) after the initial COVID-19 diagnosis. SARS-CoV-2 IgG antibody levels were detected 4-5 weeks after the initial COVID-19 diagnosis.ICAM-1 levels in serum from a recovered COVID-19 patient were highest 5 weeks after the initial COVID-19 diagnosis. The presence of high levels of soluble markers such as ICAM-1, as measured by the anti-ICAM-1 antibody, may be due to their increased shedding from the cell surface. ICAM-1 may also be a prognostic indicator for late complications or sequelae due to COVD-19 infection.CONCLUSIONSICAM-1 levels in serum from a recovered COVID-19 patient were highest 5 weeks after the initial COVID-19 diagnosis. The presence of high levels of soluble markers such as ICAM-1, as measured by the anti-ICAM-1 antibody, may be due to their increased shedding from the cell surface. ICAM-1 may also be a prognostic indicator for late complications or sequelae due to COVD-19 infection.